Petnajst let terenskih raziskav romejščine - Sitaridou, Ioanna (Keria (Ljubljana), 2023)
Romeyka is the last surviving variety of Greek spoken in north-eastern Tur-key. Islamisation of Greek speakers in the areas of Of, Sürmene, Rize, and Matsouka, is reported in the 15th-18th centuries. Through the Exchange of Populations between Greece and Turkey in 1923, Greek-speaking Muslims were allowed to stay in their Asia Minor homeland, which explains why Greek survives only in small enclaves in this area. In this article we discuss the main findings and conclusions about Romeyka, 15 years since the first field trip to the Trabzon area. We survey the main elements of external history and its genetic classification; we provide an overview of documentation efforts for Romeyka and a brief grammatical sketch; finally, we discuss its current soci-olinguistic situation and the revitalization efforts against within a context of many ideological(ised) challenges.
Keywords: grščina; grška narečja; ogroženost; pontska grščina; romejščina; Turčija